PERANCANGAN PALANG MERAH INDONESIA KOTA MUARA TEWEH - Ega Nur Muhammad Arsi; Nurfansyah Nurfansyah (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2024)
The Indonesian Red Cross, which is often known by the abbreviation PMI, is a national association organization located in Indonesia and engaged in the humanitarian field. The activity that was first carried out by PMI was to help victims of the Indonesian Revolutionary War of Independence and return victims of Allied and Japanese prisoners of war so that the Indonesian Red Cross has gained international recognition. The purpose of the design this time is "How to design the Muara Teweh Indonesian Red Cross (PMI) building which is able to fulfill the activities of the volunteers and their working staff by providing assistance and blood services to the people in the city of Muara Teweh which are appropriate and make rooms with adequate facilities?”. By using the concept of "Local Wisdom" by prioritizing the function of building the PMI building and using the Symbolism Method in the design.